Anti-coking nano ceramic coating and construction method thereof

By adding an appropriate amount of calcium molybdate to the nanoceramic coating and using thermal spraying to form the coating, the problem of coking the coating in a high-temperature flue gas environment is solved, and the anti-coking performance and service life of the coating are significantly improved.

CN119708896AActive Publication Date: 2025-03-28HEFEI KEDE SURFACE TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510225913.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

Nanoceramic coatings are prone to coking in high-temperature flue gas environments, resulting in a decrease in thermal efficiency, an increase in energy consumption and an increase in the risk of equipment damage. The existing cleaning methods affect production and operation.

Method used

Anti-coking nanoceramic coating composed of composite powder, including nanoceramic matrix and calcium molybdate, is controlled at 7.3~10 wt%, and the coating is formed by thermal spraying.

Benefits of technology

Significantly improve the anti-coking ability of the coating, extend the service life, and effectively prevent coking in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides an anti-coking nano ceramic coating, the anti-coking nano ceramic coating is a composite powder component and comprises a nano ceramic matrix and calcium molybdate, the addition amount of the calcium molybdate in the coating is controlled to be 7.3-10 wt%, and the uniformly mixed anti-coking nano ceramic coating powder needs to be sprayed by a thermal spraying process to form a coating. After the nano ceramic coating is constructed, coatings formed on the inner wall parts of boiler equipment, flues and the like have a certain anti-coking effect, and the coking phenomenon caused by long-term contact with high-temperature flue gas can be effectively improved, so that the service life of the coatings is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of protective coatings, and in particular relates to an anti-coking nano-ceramic coating and a construction method thereof. Background Art

[0002] Nano-ceramic coating is a new type of functional coating material that combines the advantages of nanotechnology and ceramic materials. It uses nano-scale particles as fillers or active ingredients to give the coating a series of excellent properties.

[0003] Ceramic powders such as alumina and zirconia can be used to make high-temperature resistant and corrosion-resistant protective coatings. Due to differences in construction technology and coating components, the final coatings will have different performance.

[0004] When nano-ceramic coatings are used in boiler equipment, supporting water cooling equipment, smoke exhaust pipe equipment, dust removal equipment, etc., they will be exposed to high-temperature flue gas for a long time, which will cause coking on the coating surface. Coking will bring a series of adverse effects, such as decreased thermal efficiency, increased energy consumption, local overheating and increased risk of equipment damage.

[0005] The more common methods are mechanical cleaning and chemical cleaning, but once the coking tendency is strong, frequent cleaning is required, which will undoubtedly affect normal production and operation management. Therefore, how to reduce the coking tendency of the coating surface in this application scenario is a more important direction to overcome. Summary of the invention

[0006] In view of the above technical problems, this application proposes an anti-coking nano-ceramic coating and a construction method thereof. The specific technical scheme is as follows: On the one hand, the present application provides an anti-coking nano-ceramic coating, which is a composite powder component, including a nano-ceramic matrix and calcium molybdate. The amount of calcium molybdate added in the coating should be controlled at 7.3~10wt% to ensure that the nano-ceramic coating has sufficient bonding strength while improving the anti-coking ability of the formed coating. When the amount of calcium molybdate added is too low, the anti-coking ability is not obvious. When the amount of calcium molybdate added is too high, it will affect the hardness of the coating formed by the nano-ceramic coating, thereby affecting the wear resistance.

[0007] The nano-ceramic matrix is ​​one or more of silicon dioxide, aluminum oxide, zirconium oxide, titanium oxide, and magnesium oxide, and all are nano-grade powders with a particle size of 20-100 nm; the nano-ceramic matrix is, for example, aluminum oxide, for example, aluminum oxide and silicon dioxide, for example, aluminum oxide, zirconium oxide and silicon dioxide, for example, aluminum oxide and zirconium oxide.

[0008] In the optional range of 7.3~10wt%, the optimal addition amount of calcium molybdate is 8.6wt%.

[0009] In a more preferred embodiment, the nano-ceramic matrix should include silicon dioxide, and the amount of silicon dioxide added should not exceed 20wt%. In combination with actual operation, the amount of silicon dioxide added should not exceed 17.2wt%.

[0010] When silicon dioxide is included in the nano-ceramic matrix, the performance of the obtained coating can be further optimized by adding a certain amount of carbon powder, especially the ratio of the added amount of carbon powder to calcium molybdate and silicon dioxide (1-2): 2.51:2.

[0011] On the other hand, the present application also discloses a method for obtaining a coating by constructing the above-mentioned anti-coking nano-ceramic coating, which method requires the use of a thermal spraying process to spray the uniformly mixed anti-coking nano-ceramic coating powder to form a coating.

[0012] The beneficial effects of the present invention are as follows: the nano-ceramic coating of the present application forms a coating on the inner wall of boiler equipment, flue, etc. after construction, which has a certain anti-coking effect and can effectively improve the coking phenomenon caused by long-term contact with high-temperature flue gas, thereby extending the service life of the coating. DETAILED DESCRIPTION

[0013] In the following description, certain specific details are set forth in order to provide a thorough understanding of various embodiments. However, it will be appreciated by those skilled in the art that the present invention may be practiced without these details. In other cases, well-known structures are not shown or described in detail to avoid unnecessarily obscuring the description of the embodiments. Unless the context otherwise requires, throughout the specification and the appended claims, the word "comprising" shall be interpreted in an open, inclusive sense, i.e., as "including but not limited to".

[0014] Unless otherwise specified, the reagents, raw materials, etc. in the following examples and comparative examples of this application were purchased from commercial sources. Example 1

[0015] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 57.7 wt % of aluminum oxide, 35 wt % of zirconium oxide, and 7.3 wt % of calcium molybdate. Example 2

[0016] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 56.9 wt % of aluminum oxide, 35 wt % of zirconium oxide, and 8.1 wt % of calcium molybdate. Example 3

[0017] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 56.4 wt % of aluminum oxide, 35 wt % of zirconium oxide, and 8.6 wt % of calcium molybdate. Example 4

[0018] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 56 wt % of aluminum oxide, 35 wt % of zirconium oxide, and 9 wt % of calcium molybdate. Example 5

[0019] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 55.5 wt % of aluminum oxide, 35 wt % of zirconium oxide, and 9.5 wt % of calcium molybdate. Example 6

[0020] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 55 wt % of aluminum oxide, 35 wt % of zirconium oxide, and 10 wt % of calcium molybdate.

[0021] Comparative Example 1 This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 59 wt % of aluminum oxide, 35 wt % of zirconium oxide, and 6 wt % of calcium molybdate.

[0022] Comparative Example 2 This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 54 wt % of aluminum oxide, 35 wt % of zirconium oxide, and 11 wt % of calcium molybdate.

[0023] Sample preparation In Comparative Example 1, Examples 1 to 6 and Comparative Example 2, the content of zirconium oxide remains unchanged, and the content of calcium molybdate increases.

[0024] The nano-ceramic coating mixed powders of the above-mentioned Examples 1 to 6 and Comparative Examples 1 and 2 are prepared into coatings by thermal spraying, and the method is as follows: (1) Surface pretreatment: Clean the surface of the substrate to remove oil, dirt and oxides; Sandblasting is performed to increase surface roughness and improve coating adhesion; Before spraying, the substrate is usually preheated to 100°C to 300°C to reduce thermal stress and improve coating adhesion; (2) Spraying process: The dry nano-ceramic coating mixed powder is fed into the plasma spray gun through a powder feeder, and the powder feeding rate is usually 20 to 100 g / min; The powder is melted or semi-melted at high temperature and sprayed onto the surface of the substrate at high speed to form a dense coating. The spraying particle speed is about 200 to 400 m / s; the main gas (such as argon) flow rate is 30 to 60 L / min; the auxiliary gas (such as hydrogen) flow rate is 5 to 15 L / min.

[0025] (3) Cooling and post-processing: After spraying is completed, the coating is cooled naturally.

[0026] Performance Testing The hardness and anti-coking performance of the coating were tested, wherein the hardness test was conducted using the GB / T 16534-2009 standard; the anti-coking performance test was conducted by placing the prepared coated substrate in coal slag with an alkali metal content of 44.29% at 800°C for 72 hours, then taking it out and observing whether there was coking on the surface of the sample.

[0027] The performance test results are shown in Table 1:

[0028] In Table 1, the anti-coking performance “ / ” indicates that no coking phenomenon occurs, and “%” indicates that coking occurs on the surface of the sample coating, and the coking area accounts for the proportion of the total area of ​​the sample coating.

[0029] Combined with the results in Table 1 above, it can be seen that with the increase in the amount of calcium molybdate added, the hardness value of the coating gradually decreases, and the anti-coking performance gradually improves. On the one hand, according to the recommendation of standard T / CEC 685-2022 "Technical Specifications for High-Temperature Nano-Ceramic Identification Coatings for Boiler Heating Surfaces", the hardness of the coating should be greater than 800 HV, so the amount of calcium molybdate added should not exceed 10wt%. On the other hand, in order to avoid coking during actual use of the coating, the amount of calcium molybdate added should not be less than 7.3wt%, otherwise the coking phenomenon of the coating will be more obvious. At the same time, it was observed that when the amount of calcium molybdate added reached 8.6wt%, it began to stabilize and no coking occurred, so 8.6wt% is a better addition value of calcium molybdate. Example 7

[0030] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 74.2 wt % of aluminum oxide, 17.2 wt % of silicon dioxide, and 8.6 wt % of calcium molybdate. Example 8

[0031] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 78.17 wt % of aluminum oxide, 13.23 wt % of silicon dioxide, and 8.6 wt % of calcium molybdate. Example 9

[0032] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 80.65 wt % of aluminum oxide, 10.75 wt % of silicon dioxide, and 8.6 wt % of calcium molybdate.

[0033] Comparative Example 3 This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 66.4 wt % of aluminum oxide, 25 wt % of silicon dioxide, and 8.6 wt % of calcium molybdate.

[0034] Comparative Example 4 This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 56.4 wt % of aluminum oxide, 35 wt % of silicon dioxide, and 8.6 wt % of calcium molybdate.

[0035] Sample preparation In Comparative Example 4, Comparative Example 3, and Examples 7 to 9, the content of calcium molybdate remains unchanged, and the content of silicon dioxide decreases.

[0036] The nano-ceramic coating mixed powders of the above-mentioned embodiments 7 to 9 and comparative examples 3 and 4 were made into coatings by thermal spraying, and the method was the same as that of the above-mentioned embodiment 1.

[0037] Performance Testing The hardness, anti-coking performance and thermal shock resistance of the coating were tested, wherein the hardness test adopted GB / T 16534-2009 standard; the anti-coking performance was tested by placing the prepared substrate with coating in coal slag with an alkali metal content of 44.29% at 800°C for 120 hours, and then observing whether there was coking on the surface of the sample; the thermal shock resistance was tested by heating the prepared substrate with coating to 1000°C, quenching in cold water, and after 40 cycles, observing the cracking and shedding of the coating.

[0038] The performance test results are shown in Table 2:

[0039] In Table 2, the anti-coking performance “ / ” indicates that there is no coking phenomenon, “%” indicates that coking occurs on the surface of the sample coating, and the proportion of the coking area to the total area of ​​the sample coating, “No” indicates that the sample coating does not crack or fall off, and “Yes” indicates that the sample coating cracks or falls off.

[0040] Combined with the results in Table 2 above, it can be seen that after replacing zirconium oxide with silicon dioxide, the greater the amount of silicon dioxide added, the greater the impact on the hardness of the coating, and the amount of silicon dioxide added should not exceed 25%, or the amount of silicon dioxide added should be at least less than 25%, or even lower, to ensure the basic hardness requirements of the coating; on the other hand, the thermal shock resistance is tested. Since the thermal expansion mismatch between excessive silicon dioxide and the ceramic matrix material aggravates the thermal stress and reduces the thermal shock resistance, the amount of silicon dioxide added should be controlled within a relatively low range; secondly, when testing the anti-coking performance, the insulation time was extended, and it was also found that when the amount of silicon dioxide added was lower, better anti-coking performance could be obtained. The better choice is a silicon dioxide addition of 10.75wt%, at which time the mass ratio of silicon dioxide to calcium molybdate is 1:0.8. Example 10

[0041] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, which includes 78.5 wt % of aluminum oxide, 10.75 wt % of silicon dioxide, 8.6 wt % of calcium molybdate and 2.15 wt % of carbon powder. Embodiment 11

[0042] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 76.36 wt % of aluminum oxide, 10.75 wt % of silicon dioxide, 8.6 wt % of calcium molybdate, and 4.29 wt % of carbon powder. Example 12

[0043] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 74.21 wt % of aluminum oxide, 10.75 wt % of silicon dioxide, 8.6 wt % of calcium molybdate, and 6.44 wt % of carbon powder. Embodiment 13

[0044] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 72.07 wt % of aluminum oxide, 10.75 wt % of silicon dioxide, 8.6 wt % of calcium molybdate, and 8.58 wt % of carbon powder. Embodiment 14

[0045] This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 71.73 wt % of aluminum oxide, 13.23 wt % of silicon dioxide, 8.6 wt % of calcium molybdate and 6.44 wt % of carbon powder.

[0046] Comparative Example 5 This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 69.93 wt % of aluminum oxide, 10.75 wt % of silicon dioxide, 8.6 wt % of calcium molybdate and 10.72 t % of carbon powder.

[0047] Comparative Example 6 This embodiment provides 10 kg of an anti-coking nano-ceramic coating, wherein the nano-ceramic coating includes 84.04 wt % of aluminum oxide, 7.36 wt % of silicon dioxide, and 8.6 wt % of calcium molybdate.

[0048] Sample preparation In Examples 10 to 13 and Comparative Example 5, the contents of silicon dioxide and calcium molybdate remain unchanged, and the content of carbon powder increases; in Example 14 and Example 12, the contents of calcium molybdate and carbon powder are the same, and the silicon dioxide content in Example 14 is greater than that in Example 12; Comparative Example 6 does not contain carbon powder, and the silicon dioxide content is lower than that in Example 12.

[0049] The nano-ceramic coating mixed powders of the above-mentioned embodiments 10 to 13 and comparative examples 5 and 6 were made into coatings by thermal spraying, and the method was the same as that of the above-mentioned embodiment 1.

[0050] Performance Testing The hardness, anti-coking performance, thermal shock resistance and high temperature resistance of the coating were tested, wherein the hardness test was conducted using the GB / T16534-2009 standard; the anti-coking performance test was conducted by placing the coated substrate in coal slag with an alkali metal content of 44.29% at 800°C for 120 hours, then taking it out and observing whether there was coking on the surface of the sample; the thermal shock resistance test was conducted by heating the coated substrate to 1000°C, quenching it in cold water, and observing the cracking and shedding of the coating after 40 cycles; the high temperature resistance test was conducted by keeping the coated substrate at 1400°C in an air atmosphere for 10 hours, then observing the cracking and shedding of the coating.

[0051] The performance test results are shown in Table 3:

[0052] In Table 3, for the anti-coking performance, “ / ” indicates that there is no coking phenomenon, and “%” indicates that coking occurs on the surface of the sample coating, and the proportion of the coking area to the total area of ​​the sample coating; for the thermal shock resistance performance, “no” indicates that the sample coating does not crack or fall off, and “yes” indicates that the sample coating does crack or fall off; for the high temperature resistance performance, “no” indicates that the sample coating does not crack or fall off.

[0053] Combined with the results in Table 3 above, it can be seen that after adding a certain amount of carbon powder, the hardness of the coating will be affected, and as the amount of carbon powder added increases, the hardness of the coating shows a trend of first increasing and then decreasing. When the amount of carbon powder added is 4.29~8.58wt%, the hardness of the coating can be improved. At the same time, the addition of carbon powder can improve the anti-coking performance of the coating. Since the addition amounts of calcium molybdate and silicon dioxide remain unchanged, the mass ratio of calcium molybdate, silicon dioxide and carbon powder should be considered, that is, 2.51:2:(1~2), and the preferred ratio of the three should be 2.51:2:1.5.

[0054] The above embodiments are only used to illustrate the technical solutions of the present invention, but not to limit them.

Claims

1. An anti-coking nano-ceramic coating, characterized in that: The invention comprises a nano ceramic matrix and calcium molybdate, wherein the addition amount of the calcium molybdate is 7.3-10wt%.

2. The anti-coking nano-ceramic coating according to claim 1, characterized in that: The added amount of calcium molybdate is 8.6wt%.

3. The anti-coking nano-ceramic coating according to claim 1, characterized in that: The nano-ceramic matrix includes silicon dioxide, and the added amount of the silicon dioxide does not exceed 17.2wt%.

4. The anti-coking nano-ceramic coating according to claim 3, characterized in that: The added amount of the silicon dioxide does not exceed 10.75wt%.

5. The anti-coking nano-ceramic coating according to claim 3, characterized in that: Also includes toner.

6. The anti-coking nano-ceramic coating according to claim 5, characterized in that: The mass ratio of the calcium molybdate, silicon dioxide and carbon powder is 2.51:2:(1~2).

7. The anti-coking nano-ceramic coating according to claim 6, characterized in that: The mass ratio of the calcium molybdate, silicon dioxide and carbon powder is 2.51:2:1.

5.

8. The construction method of the anti-coking nano ceramic coating is characterized in that: The method comprises: uniformly mixing the anti-coking nano-ceramic coating powder according to any one of claims 1 to 7 and then forming a coating by a thermal spraying process.

9. The construction method of the anti-coking nano-ceramic coating according to claim 8, characterized in that: Before thermal spraying, the substrate to be sprayed is subjected to surface pretreatment, and the surface pretreatment includes cleaning and / or sandblasting.

Citation Information

Patent Citations

  • Oil soluble molybdenum complexes as high temperature fouling inhibitors

    CA3147908A1

  • Water wall refractory belt anti-coking paint

    CN102351553A

  • Anti-coking coating and preparation process thereof

    CN114196238A

  • Anti-coking and anti-ash coating for receiving surface of waste heat boiler and preparation method of anti-coking and anti-ash coating

    CN117004291A

  • Anti-corrosion and Anti-coking ceramic coating with easy state identification for coal-fired boiler and preparation method thereof

    US20230060480A1